Catheter-related thrombosis in a neonatal intensive care unit: a case-control study - Valente, Cristina Ortiz Sobrinho; Silva, Júlia Gomes da; Savioli, Ana Paula Farias; Ganéo, Emilly Giuliane; Lebrão, Cibele Wolf; Costa, Gleise Aparecida Moraes (ABCS Health Sciences, 2024)
Introduction: Catheter-related thrombosis (CRT) accounts for most thrombotic events in the neonate. Objective: Investigate CRT frequency, association with days of catheter use until diagnosis, and number of catheters used, in a single-center Neonatal Intensive Care Unit. Methods: A case-control study that included 14 cases and 42 controls. Data collection occurred between January 2017 and December 2020 in a public NICU. Crude odds ratios (COR) were calculated. The study complied with ethical standards from national guidelines. Results: Two hundred and ninety-four neonates used central venous catheters, of which 14 (4.7%) were diagnosed with CRT. Catheter in use when diagnosis was made was centrally inserted central catheters in 8 (57.1%). Before diagnosis, the cumulative duration of catheter use was 34.5 days and the median number of catheters used was three. A higher SNAPPE-II (COR 1.03; 95% CI 1.01-1.06; p=0.03), cumulative days of catheter use >30 (COR 19.11; 95% CI 2.28-160.10; p=0.007) and number of catheters used >3 (COR 7.66; 95% CI 1.51-38.70; p=0.01) were associated with CRT. Conclusion: CRT cases were associated with clinical severity; number of catheters and cumulative days of catheter use. We suggest that screening for thrombosis should be performed in neonates who need a long time of catheter use and more than three catheters. Reducing the duration and number of venous catheters used will help to reduce CRT.